The education values of full-time and part-time students of a ministerial university - Oleg Victorovich Filimonov; Dmitry Grigorievich Perednya (Вестник Майкопского государственного технологического университета)
The article is based on the results of the sociological study on the value orientations of students in two traditional forms - full-time and part-time, the peculiarities of their educational trajectories, the motivation for choosing the form of education. The article tests the hypothesis about the presence (absence) of a pronounced connection between the organizational form of education at a university and the subsequent distribution of students, based on estimates of their level of education. The collection of empirical material on the research problem has been carried out in the course of planned research work devoted to the study of the image of the Academy of Management of the Ministry of Internal Affairs of Russia. A number of associations about the university among those who received education in different forms of education have been identified and described Two approaches of value expectations from education have been identified : the first is closely related to the strengthening of the resource of the prestige of academic education, the second - with the increase in the educational potential of the educational institution. It has been proved that in full-time students the desire to improve themselves as individuals and professionals who can compete on the basis of improved personal competencies, and not on the symbolic attributes of the social hierarchy prevail; the educational efforts of a significant part of students by correspondence are focused mainly on achieving a formal learning outcome - an increase in status, and do not consider a diploma as a document that reflects the qualifications and level of education of the owner. The article makes a substantiated conclusion about the need to differentiate the status of the received educational document depending on the form of study at a university.